Preparation of activated carbon from pink guava (Psidium guajava) waste for the removal of methylene blue dye from aqueous solution / Nurulhuda Amri, Mohammad Syazwan Osman and Rasyidah Alrozi - Osman, Mohammad Syazwan; Alrozi, Rasyidah (Research Management Institute (RMI), 2012)
Activated carbons are the most versatile and commonly used adsorbents because of their extremely high surface areas and micropore volumes, large adsorption capacities, fast adsorption kinetics and relative ease of regeneration. The most precursors used for the production of activated carbons are organic materials that are rich in carbon. In recent years, agricultural wastes has gained a significant interest among researches and being economic and eco-friendly due to their unique chemical composition, availability in abundance, renewable, low in cost and more efficient seem to be possible option for dye removal. Thus, the main objective of this research is to prepare activated carbon from pink guava waste (PGW) using simple thermochemical activation method. The raw material will be carbonized carbonized at temperature of 400°C for 1 h in a muffle furnace in order to produce char. Then, the char will be impregnated with sodium hydroxide (NaOH) at different impregnation ratios (1- 3) by weight followed by activation process at activation temperatures (400°C - 600°C) under different activation time (0.5 - 2 h). The optimize conditions for the preparation of activated carbon will be determined using Response Surface Methodology (RSM) with response to the activated carbon yield and percentage removal of methylene blue (MB) dye onto the adsorbent in order to obtain high adsorption capacity of the MB dye. The prepared pink guava seed based activated carbon (ACPGS) obtained by optimum conditions will be characterized through Brunauer Emmett Teller (BET) surface area, Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR) and Elemental Analyzer (EA). Then, the comparison on adsorption performance between ACPGW and commercial activated carbon (CAC) will be done using the batch adsorption study to determine the adsorption capacity for both adsorbents. The batch adsorption study will be carried out at different initial concentrations of methylene blue (50-500 mg/L) at room temperature (30°C) for 6 h. This research will explore the potential application of a low cost adsorbent to replace the commercial activated carbon for removal of dyes from wastewater.